RASIO KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PERUSAHAAN PT CITRA MAHKOTA AMBAWANG - Amelia, Amelia; Diana, Tri; Noviryantika, Noviryantika (STIE 'INDONESIA' Pontianak, 2025)
The purpose of this research is to assess the financial performance of PT. Citra Mahkota Ambawang during the 2022-2024. Period based on liquidity, solvency, and profitability ratios. The population of this research is the annual financial report of PT. Citra Mahkota Ambawang for the period 2022-2024. The sampling technique uses a non-probability sampling method with a saturated sampling approach, namely the financial report of PT. Citra Mahkota Ambawang which includes the Balance Sheet and Profit and Loss Report for 2022-2024. This research is quantitative with a comparative analysis method using the Year-to-year Changes Analysis. The research results show that in terms of liquidity and solvency ratios the performance is quite than optimal because cash and cash equivalents have been able to fulfill all their obligations. From the profitability aspect, the company is able to generate profits and use assets efficiently based on GPM, NPM and ROI indicators.